Development and validation of a method for the quantification of fructooligosaccharides in a prebiotic ice cream - Claudia L. González-Aguirre; Juan S. Ramírez-Navas (GarVal Editorial Ltda., 2018)
Context: Fructooligosaccharides (FOS) are known as oligofructanes, oligosaccharides or oligofructose, which fall within the concept of prebiotics. One of the methods most commonly used in the industry for quantification and quality control nutraceutical substances classification is the method of high performance liquid chromatography (HPLC). Aims: To develop a procedure for the determination of FOS by HPLC in raw materials and a prebiotic ice cream. Methods: For the chromatographic separation, an HPLC was used with a refractive index detector (IR). The separation was performed using two columns coupled Sugar-pak I™ using an isocratic procedure with water type 1 at 0.35 mL/min. Kestose (GF2), nistose (GF3) and fructofuranosylnystose (GF4) were used as standards. Robustness was assessed by applying the Youden and Steiner test. Results: Good linear correlations were obtained (y = 14191.4470 x + 285684.2, r2 = 0.9904) within the concentration range of 8.0-12.0 mg/mL. The FOS recoveries were 99.5% with the intra-day and inter-day relative standard deviation (RSD) less than 0.8%. The robustness test showed that the temperature parameters of the column and flow velocity are critical factors in the method. Conclusions: This reliable, simple and cost-effective method could be applied to the routine monitoring of FOS (GF2, GF3, and GF4) in raw materials and prebiotic ice creams.